Finishing of wire electric discharge machined surface - Rajaram, Attukur Nandagopal (Nanyang Technological University, 2016)
Wire Electric Discharge Machining (WEDM) has been employed to intricately cut and fabricate structures from hard metal alloys like Inconel. It is a non-contact process that can be used to fabricate structures without causing any or minimal dimensional distortions. However, the formation of recast layer on the structure surface during fabrication greatly reduces the fatigue strength of the structure and also induces micro cracks and tensile residual stress into the surface. This project aims in identifying a surface finishing method and determine the feasibility of using it to remove the recast layer. A simple cylindrical test coupon is fabricated by WEDM process and the selected surface finishing method is used to finish the coupon. Surface characterization is performed before and after finishing the coupon surface to validate the removal of recast layer. Scanning Electron Microscope (SEM) is used for visual inspection, Energy Dispersive X-ray spectroscopy (EDX) is used for chemical characterization and X-Ray Diffraction is used to measure the residual stress. The surface characterization results showed that recast layer could be removed from Wire Electric Discharge Machined surface using Abrasive Flow Machining without inducing any tensile residual stresses.